2018
DOI: 10.1002/ajhb.23108
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific patterns in cortical and trabecular bone microstructure in the Kirsten Skeletal Collection, South Africa

Abstract: This research highlights sex-specific differences in patterns of age-related bone loss, and provides context for discussion of contemporary South African bone health. While the study sample demonstrates indicators of poor bone quality, osteoporosis research continues to be under-prioritized in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 105 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…The objective of this research was to explore age‐ and sex‐related patterns in the structural and material properties of mid‐thoracic ribs to help build an understanding of apartheid health conditions in predominately non‐white South Africans. Results echo our previous work on bone mass and microstructure in a similar subset of the Kirsten Skeletal Collection (Beresheim et al, ; Pfeiffer et al, ). Sex‐related variation in remodeling differentially impacts skeletal aging in this sample.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The objective of this research was to explore age‐ and sex‐related patterns in the structural and material properties of mid‐thoracic ribs to help build an understanding of apartheid health conditions in predominately non‐white South Africans. Results echo our previous work on bone mass and microstructure in a similar subset of the Kirsten Skeletal Collection (Beresheim et al, ; Pfeiffer et al, ). Sex‐related variation in remodeling differentially impacts skeletal aging in this sample.…”
Section: Resultssupporting
confidence: 89%
“…Health status is assumed to be relatively poor for most individuals in this sample, given available epidemiological data for non‐whites living on the Western Cape at this time (Inwood & Masakure, ; Mpeta & Inwood, ; Williams et al, ). This presumption is also supported by cadaver donation sources, cause of death information, and previous research conducted on the broader Kirsten Skeletal Collection (Alblas et al, ; Beresheim, Pfeiffer, Grynpas, & Alblas, ; Geldenhuys, Burger, Alblas, Greyling, & Kotze, ; Labuschagne & Mathey, ).…”
Section: Discussionmentioning
confidence: 67%
“…Micro-CT has been proposed as a minimally destructive way to investigate taphonomically significant changes to bone (Dal Sasso et al 2014). It has been shown to be a useful tool for identifying bone bio-erosion, wherein eroded areas have a lower relative density than unaffected bone (Booth et al 2016). Similarly, the intake of extraneous matter from the post-depositional environment can increase the density of the bone tissue (Mays, 2007).…”
Section: Diagenesis and Bmdmentioning
confidence: 99%
“…Also, a socio‐economic enquiry conducted in the region of Coimbra in 1906 showed that food rations for women were both quantitatively and qualitatively inferior (Pereira, ). In skeletal samples, the cortical bone has been shown to decrease with age in both males and females (Beauchesne & Agarwal, ; Beresheim, Pfeiffer, Grynpas, & Alblas, ; Ives, ; Mays, ) or only in females (Mays, ; Umbelino et al, ). Other studies at the CISC also suggest that cortical bone loss in males is negligible (Bergot et al, ; Curate & Cunha, ).…”
Section: Discussionmentioning
confidence: 99%